2022
DOI: 10.1371/journal.pgen.1010305
|View full text |Cite
|
Sign up to set email alerts
|

“The ubiquitin ligase SIAH2 is a female-specific regulator of circadian rhythms and metabolism”

Abstract: Circadian clocks enable organisms to predict and align their behaviors and physiologies to constant daily day-night environmental cycle. Because the ubiquitin ligase Siah2 has been identified as a potential regulator of circadian clock function in cultured cells, we have used SIAH2-deficient mice to examine its function in vivo. Our experiments demonstrate a striking and unexpected sexually dimorphic effect of SIAH2-deficiency on the regulation of rhythmically expressed genes in the liver. The absence of SIAH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 63 publications
2
16
0
Order By: Relevance
“…We and others have investigated how various ubiquitin ligases contribute to the degradation of REV-ERB and their effects on the circadian clock (12)(13)(14)(15)(16). In this study, we focused on trying to understand the central events that need to happen to REV-ERB protein itself for degradation to take place.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and others have investigated how various ubiquitin ligases contribute to the degradation of REV-ERB and their effects on the circadian clock (12)(13)(14)(15)(16). In this study, we focused on trying to understand the central events that need to happen to REV-ERB protein itself for degradation to take place.…”
Section: Discussionmentioning
confidence: 99%
“…Lanes "M" were lysates from cells treated with MG132 for 3 hours (lanes 6, 12, 18, and 24). C. WT and the rearranged mutant AA2-9insAA25 were co-transfected with Sport6 (lanes 1-12) or Sport6-SPSB4 (lanes [13][14][15][16][17][18][19][20][21][22][23][24], into HEK293 cells. 36-48 hours after transfection, cells were treated with cycloheximide for the indicated number of hours, and the Western blot was probed with anti-REV-ERB antibody Lanes "M" were lysates from cells treated with MG132 for 4 hours (lanes 6, 12, 18, and 24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, 23 of 44 unique tissues had samples only from males, whereas 16 tissues had samples in some way from females (as female only, male and female, or mixed; Supplemental Table S7 ). Within liver, by far the most common tissue, 46 of 60 studies were male only, whereas 5 were female only and 5 were male and female ( Vollmers et al, 2009 ; Yang et al, 2016 ; Sato et al, 2017 ; Weger et al, 2019 ; Mekbib et al, 2022 ) ( Supplemental Table S8 ). In humans, the most common tissue was blood, for which 6 of 9 studies included males and females.…”
mentioning
confidence: 99%
“…Second, the underrepresentation of females in transcriptome experiments was concordant with that of other experiments. Third, of the 9 studies that included males and females for any experiment, 2 reported results by sex ( Jouffe et al, 2022 ; Mekbib et al, 2022 ).…”
mentioning
confidence: 99%